Tanahku Indonesia: Celebrating the Indigenous Interior - Johanes, Mikhael; Wahid, Arif Rahman (UI Scholars Hub, 2018)
Tanahku Indonesia was a week-long, architecture and interior design exhibition showing local earth-based materials to reveal their potential as an integral part of Indonesia’s creative economy development. Curated by Yandi Andri Yatmo and Paramita Atmodiwirjo, the exhibition was held in dia.lo.gue Artspace in Central Jakarta, Indonesia from 8 to 12 November 2017. This exhibition attempted to reveal the materiality of earth-based materials across a broad spectrum, which was not limited to the physical presence of the materials, but more as a reflection of knowledge that was grounded on the deep understanding of their context. This multifaceted exhibition showed various earth-based materials gathered from different places within the Indonesian archipelago, as well as the methods and techniques related to the materials, while also revealing their values within architectural and interior design practice in Indonesia.